La riqueza de los bosques mexicanos: mas alla de la madera: experiencias de comunidades rurales - López, C.; Chanfon, S.; Segura, G. (Secretaria de Medio Ambiente y Recursos Naturales (Semarnat) and CIFOR, 2005)
The book contains 19 non-timber forest products (NTFPs) cases representing the main ecological areas of Mexico and written by experts in collaboration with technicians and local producers. The aim of the book is to promote the exchange of knowledge and experiences about NTFPs among mexican rural communities.